2018
DOI: 10.1002/cche.10105
|View full text |Cite
|
Sign up to set email alerts
|

Textural and cooking qualities of dry Laksa noodle made from semi‐wet and wet MR253 flours

Abstract: Background and objectives: The purpose of this study was to investigate the effect of semi-wet and wet ground rice flours from MR253 rice variety on the cooking, textural, and sensorial qualities of dry rice noodle (laksa noodle). This rice flour is classified as a medium group of amylose content of 20.27% in semiwet and 20.59% in wet, respectively. Findings: Pearson correlation analysis of these flours implies that amylose content, percentage of damaged starch granule, and water absorption of rice flour incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The above results indicated that damaged starch content increased after SS treatment, which was consistent with the results of damaged starch determination. Additionally, we also inferred in Section 3.2 that the starch in wheat grains treated with SS was easier to damage during milling for the loss of moisture (Ahmad & Rajab, 2018; Wang et al, 2020). The aggregation and damage of wheat starch significantly increased the water absorption and gelatinization temperature of wheat flour (Liu, Song, et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The above results indicated that damaged starch content increased after SS treatment, which was consistent with the results of damaged starch determination. Additionally, we also inferred in Section 3.2 that the starch in wheat grains treated with SS was easier to damage during milling for the loss of moisture (Ahmad & Rajab, 2018; Wang et al, 2020). The aggregation and damage of wheat starch significantly increased the water absorption and gelatinization temperature of wheat flour (Liu, Song, et al, 2020).…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the moisture of wheat endosperm significantly decreased with the extending of steam temperature and treatment time. Since starch was easy to damage at a low moisture during milling, milling‐damaged starch significantly increased as the steam temperature and treatment time increased (Ahmad & Rajab, 2018; Ghodke et al, 2009; Wang et al, 2020). In consequence, the control of wheat moisture, steam temperature, and treatment time are important for controlling the change of damaged starch contents following SS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Wet‐milled highland barley flour showed higher total starch content than DBF, which was ascribed to the milling temperature during the milling process. Wet milling allowed water to absorb the heat generated by the machine and reduce the temperature (Ahmad & Rajab, 2018). While the high temperature generated in the dry milling could lead to the gelatinization of some starch in HBF.…”
Section: Resultsmentioning
confidence: 99%
“…Li, Yuan et al (2019) reported that the commercial pulse starches obtained from wet milling exhibited smooth surfaces, whereas the air-classified pea, lentil, and faba bean starches displayed broken granules and scratches on the surface. Ahmad et al (2018), in their study on Laksa noodles developed from semi-wet and wet rice flours, explained that the reduced starch damage observed in the wet milling process was due to excess water added in the milling. This excess water buffers the elevated temperature of the grinding machines by absorbing the heat generated, consequently leading to less starch damage.…”
Section: Starch Damagementioning
confidence: 99%